Volatilitas Arus Kas dan Volatilitas Penjualan Terhadap Persistensi Laba - Rahmad Arif; Febryandhie Ananda (Pusat Riset dan Inovasi Nasional, 2023)
Profit persistence is the productive persistence of correcting future profits which is expected to be reflected in the innovation of profit in the current year in order to receive continuous profit from the innovation of profit in the current year and the use of proven company assets. One of the causes of the low quality of results is the result of the intention of management to consciously engage in the management of results in the process of determining profits in order to fulfill the tasks assigned by the owner, as well as motives for the fulfillment of personal goals. This study aims to find out and analyze how much influence Cash Flow Volatility (X1) Sales Volatility (X2) has on Profit Persistence (Y) on consumer goods industry sector companies on the Indonesia Stock Exchange. The method carried out in this study is quantitative using secondary data in the form of annual reports of companies in the consumer goods industry sector for the 2018 – 2021 period. The analysis technique used is panel data regression. Based on the results of the study (X1) Cash Flow Volatility has a positive effect on Profit Persistence in consumer goods industry sector companies on the Indonesia Stock Exchange, and (X2) Sales Volatility negatively affects Profit Persistence in consumer goods industry sector companies on the Indonesia Stock Exchange.